Human Resources Administration: a comparative analysis of two companies - Canabal-Herrera , Ignacio J. (2024)
This article shows a comparison in the Administration of human capital in two organizations, the Drinking Water and Sanitation System (SAS), a decentralized body of the Municipality of the Center of the state of Tabasco and the Circle K Corporate. The objective of the article was to analyze Comparative processes of human resources administration of both organizations through a qualitative methodology. The data collection technique used consisted of semi-structured interviews with the managers of both organizations, whose transcription was carried out with the Atlas.ti 9 software, through the use of categories and the generation of quotes and codes. The results indicate that human resources management is essential in both SAS and Circle K, because through it there is operational efficiency, talent is retained and standards are met, concluding that in both organizations employees are developed with resilience.